Post-match video-based feedback: A longitudinal work-based coach development program stimulating changes in coaches` knowledge and understanding - Raya-Castellano, P. E.; Reeves, M. J.; Fradua-Uriondo, L.; McRobert, A. P. (International Journal of Sports Science & Coaching, 2021)
The literature regarding formal coach education and development highlights issues of transference of usable knowledge to the real-world context. This study sought to engage coaches from a Spanish football academy in a longitudinal work-based coach development program (CDP) focused on the delivery of post-match feedback. The CDP was delivered over a 23-month period through collaboration between a sport pedagogue researcher-practitioner, the Academy Management Team, and an experienced research team. The study adopted a case study design, utilizing a multiple method data collection strategy that occurred in several stages: 1) Systematic observations (Sep-Dec 2018) and 2) debrief (Jan 2019), where baseline coach behaviors and underpinning knowledge were recorded; 3) a workshop and a directed task (Mar 2019), encouraging coaches to apply new knowledge; 4) a directed task 2 and reflective interview (Apr/May 2019), facilitating coaches` reflection on their past deliveries and rationalization and planning of their forthcoming sessions` delivery and 5) a consolidation interview (Apr 2020), capturing knowledge stabilization. Qualitative data suggest that there was an increased understanding in the adoption of behaviors including corrective feedback, silence, questioning, and player participation throughout the CDP. In addition, coaches` self-reflection found acceptance of their coaching delivery or a disconnect between their desired and actual behaviors during the delivery of video-based feedback. This study provides a preliminary framework for further implementation and exploration in developing coaches` knowledge and understanding of delivering post-match video-based feedback.